In vitro Generation of Megakaryocytes and Platelets - Liu, Huicong; Liu, Jiaqing; Wang, Lingna; Zhu, Fangfang (Frontiers in Cell and Developmental Biology, 2021)
Platelets, the tiny anucleate cells responsible for stopping bleeding through thrombosis, are derived from hematopoietic stem cells through a series of differentiation steps. Thrombocytopenia, characterized by abnormally low blood platelet counts, may arise from cancer therapies, trauma, sepsis, as well as blood disorders, and could become a life-threatening problem. Platelet transfusion is the most effective strategy to treat thrombocytopenia, however, the source of platelets is in great shortage. Therefore, in vitro generation of platelets has become an important topic and numerous attempts have been made towards generating platelets from different types of cells, including hematopoietic stem cells, pluripotent stem cells, fibroblast cells and adipose-derived cells. In this review, we will detail the efforts made to produce, in the in vitro culture, platelets from these different cell types. Importantly, as transfusion medicine requires a huge number of platelets, we will highlight some studies on producing platelets in a large scale. Although new methods of gene manipulation, new culture conditions, new cytokines and chemical compounds have been introduced in platelet generation research since the first study of hematopoietic stem cell-derived platelets nearly 30 years ago, limited success has been achieved in obtaining truly mature and functional platelets in vitro, indicating the studies of platelets fall behind those of other blood cell types. This is possibly because megakaryocytes, which produce platelets, are very rare in blood and marrow. We have previously developed a platform to identify new extrinsic and intronic regulators for megakaryocytic lineage development, and in this review, we will also cover our effort on that. In summary, stem cell-based differentiation is a promising way of generating large-scale platelets to meet the clinical needs, and continuous study of the cellular development of platelets will greatly facilitate this.